Securing Automatic Identification System Communications Using Physical-Layer Key Generation Protocol - Jingyu Sun; Zhimin Yi; Ziyi Zhuang; Shengming Jiang (Journal of Marine Science and Engineering)
The automatic identification system (AIS) is an essential tool for modern ships, enabling the broadcast of identification and location information. However, the current AIS standard lacks security features, meaning that messages exchanged via AISs are transmitted in plaintext, which leads to security issues such as privacy leakage. Most existing solutions rely on public key cryptography. This paper proposes a physical-layer key generation protocol based on the current AIS standard (ITU-R M.1371-5). In the case of unicast AIS communication, the protocol utilizes channel randomness to generate symmetric keys for securing communications. Compared to public key cryptography, the proposed protocol offers advantages such as low overhead, elimination of third parties, and ease of implementation. Finally, this paper discusses the security of the protocol against various threats as well as evaluates its performance and overhead. Under common speed and signal-to-noise ratio (SNR) conditions, The protocol generates Advanced Encryption Standard (AES) keys of different lengths in under 4000 ms, and these keys successfully pass the National Institute of Standards and Technology (NIST) randomness test.